PROPERTY ANALYSIS OF SODIUM ALGINATE FROM BROWN MACROALGAE (Sargassum cinctum J.Agardh) - R. PRAGATHEESWARI (The Journal of Research ANGRAU, 2024)
The purpose of the study was to examine the characteristics of sodium alginate that was collected in November 2019 from Sargassum cinctum J. Agardh in the Indian Gulf of Mannar locations. Using a standardized extraction procedure, sodium alginate was extracted from Sargassum cinctum J. Agardh and was subjected to elemental composition profile analysis with Energy Dispersive X-ray spectroscopy (EDX) and morphological analysis through a Field Emission Scanning Electron Microscope (FESEM) along with 3-dimensional optical profile analysis. Heavy metal residue analysis of mercury, lead, cadmium, chromium, and arsenic done through an Atomic Absorption Spectrophotometer (AAS) at ppm level, revealed the absence (lower than the detectable limit) of arsenic and lead indicating the safety of the extracted biopolymer sodium alginate.Lethality assessment conducted with brine shrimps for 24 h revealed a higher mortality rate on increased sample content after 8 h of exposure.The outcome of the study indicated that sodium alginate from Sargassum cinctum possesses higher application potential in various sectors including food, agriculture,textile, pharmaceutical, and cosmetic industries.